THE ROLE OF THE INTERPERSONAL COMMUNICATION OF CHRISTIANITY TEACHERS IN IMPROVING THE SPIRITUAL GROWTH OF GRADE IX STUDENTS IN SMP NEGERI 2 SIANTAR - BANGUN MUNTE; Erni Murniarti (Jurnal Dinamika Pendidikan, 2018)
ABSTRAK Tujuan penelitian ini adalah untuk melihat sejauhmana Peran Komunikasi Interpersonal Guru PAK dalam meningkatkan pertumbuhan rohani siswa kelas IX di SMP NEGERI 2 SIANTAR. Jumlah sampel sebanyak 53 orang. Penelitian ini menggunakan metode deskriptif, sedangkan analisis data yang dilakukan dalam penelitian hipotesis adalah korelasi product moment pearson dengan alat pengumpulan data adalah angket untuk Variabel X (Peran Komunikasi Interpersonal Guru PAK) dan Variabel Y (Pertumbuhan Rohani Siswa). Untuk mengetahui sejauhmana Peran Komunikasi Interpersonal Guru PAK dalam meningkatkan pertumbuhan rohani siswa, maka digunakan Uji Statistik Korelasi Product Moment Pearson. Dari hasil pengujian diperoleh pengujian korelasi (r) 0,33 dengan uji determinasi sebesar 10.89% dan untuk mengetahui signifikan tidaknya koefisien korelasi pada taraf nyata (ð›¼) = 0,05 maka diadakan uji â€œtâ€ dengan kriteria pengujian jika thitung yang didapat dari perhitungan lebih besar (>) dari ttabel pada taraf signifikan 1 â€“ 0,05 dengan dk = n â€“ 2 maka hipotesis diterima dan dalam hal lain ditolak. Dari hasil pengujian diperoleh thitung > ttabel( 2,49> 1,67 ), maka hipotesis diterima. Dengan demikian dapat dikemukakan bahwa terdapat pengaruh yang signifikan dari Peran Komunikasi Interpersonal Guru PAK dalam meningkatkan pertumbuhan rohani siswa di SMP NEGERI 2 SIANTAR Kata Kunci: komunikasi interpersonal, pertumbuhan rohani siswa ABSTRACT The aim of this research is to find out the Role of the Interpersonal Communication of PAK Teacher in improving spiritual growth of Grade IX Studnets in SMP Negeri 2 Siantar. The number of samples is 53 students. This research applies descriptive method; meanwhile data analysis used for hypothesis testing is Pearsonâ€˜ product-moment correlation, of which the instruments of data collection are questionnairs for variable X (Role of interpersonal communication of PAK Teacher) and variable Y (the spiritual growth of students). To examine the Role of the Interpersonal Communication of PAK Teacher in improving spiritual growth, correlation product moment of Pearson was used as the statistical measurement. The data analysis showed that correlation (r) was 0,33 with the determination value at 10.89%; and to know whether the correlation coefficient was significant or insignificant at the level of (Î±) = 0,05, t- test was conducted of which the criterion was if tcount got from the measurement was (>)higher than ttabel at the significant level of 1 â€“ 0,05 with dk = n â€“ 2, the hypothesis was accepted and vice versa. Seen from the result of data analysis, it was found that tcount > ttabel( 2,49> 1,67 ), it meant that the hypothesis was accepted. Therefore, it could be stated that there was a significant effect of the Interpersonal Communication of PAK Teacher in improving spiritual growth at IX class at SMP Negeri 2 Siantar. Keywords: interpersonal communication, students spiritual growth